Preferensi Konsumen terhadap Pepaya Calina dan Thailand - Widodo, Widodo (Benefit: Jurnal Manajemen dan Bisnis, 2023)
Fruit consumers are faced with many choices of papaya fruit that can be purchased in the market. Calina, an unknown variety, is one of the choices for papaya consumers. This study aims to analyse the types of papaya consumers’ prefer between Calina and Thai papayas and to describe the attributes of Calina and Thai papaya that consumers prefer. The approach that was applied in this research is quantitative method, focusing on consumer attitudes towards objects. The research was conducted in Gamping District, Sleman Regency, with a sample of 100 people. The applied attitude model was the Fishbein Multi-Attribute Model. Attributes of papaya that were investigated in this research were price, sweetness taste, size, flesh colour, skin texture, and appearance. A paired t-test was used to determine the type of papaya that consumers preferred, while one-way ANOVA was applied to determine the attributes of papaya that consumers preferred. The results showed that consumers prefer Calina papaya compared to Thai papaya. One-way ANOVA analysis showed that the attributes of Calina papaya that consumers preferred were skin appearance and sweetness taste, while the attributes of Thai papaya that were preferred by consumers were sweetness taste only.